Diagnostic accuracy of monofilament test to detect diabetic neuropathy - Shrestha, Sujan; Gorhaly, Mamen Prasad; Bajracharya, Manil Ratna (Journal of Advances in Internal Medicine, 2021)
Background Diabetic peripheral neuropathy (DPN) is a significant independent risk factor for diabetic foot, and an effective screening instrument is required to diagnose DPN early to prevent future ulceration and amputation. This study aims to determine the diagnostic accuracy of monofilament test to detect diabetic peripheral neuropathy. Methods This cross-sectional study was conducted in National Academy of Medical Sciences, Bir hospital, Mahabouddha, Kathmandu from February 2016 to January 2017. A total of 96 diabetic patients attending inpatient and outpatient Department were selected. Diabetic peripheral neuropathy was assessed by measurement of loss of protective sensation (LOPS) by monofilament test and compared with vibration perception threshold by standard biothesiometer. The sensitivity, specificity, positive predictive value and negative predictive value of monofilament test were calculated. Results The prevalence of diabetic peripheral neuropathy was 26%. The sensitivity, specificity, positive predictive value and negative predictive value of monofilament test were found to be 92.0%, 95.8%, 88.5% and 97.1% respectively. There was strong association between LOPS by monofilament and vibration perception threshold by biothesiometer. Conclusion This study showed a strong diagnostic accuracy of monofilament test to detect DPN when compared with biothesiometer. As monofilament test is a cheap, easily available, and portable, it can be used in the periphery where biothesiometer is not available.